PERANAN KELUARGA, SEKOLAH DAN MASYARAKAT DALAM PEMBENTUKKAN KARAKTER ANAK DALAM PENDIDIKAN ISLAM - Ida Mariana (CV Putra Publisher, 2022)
The purpose of this research is to analyze the role of family, school and society in shaping children's character education which is very important and cannot be separated. In the family, it is the duty of parents to educate their children to be good children and have good manners and morals as well. This research method uses a qualitative approach to literature. The results of this study state that there are binding regulations in the sense of the word when there are residents who violate these rules, they will be given sanctions from traditional leaders in the community.